Studi Evaluasi Harga Minyak Mentah DuniaTerhadap Perang Rusia Ukraina - Iqbal Ilman; Nugroho Marsiyanto; Eko Prastio (Jurnal Bhara Petro Energi, 2023)
This study aims  to evaluate how the Russian-Uk rainian war affects  world crude oil prices. This conflict  plays  a significant  role in disrupting the production and supply of crude oil in the Black Sea region,  which could affect the global supply of crude oil. The evaluation method used is an analysis  of  the  latest  literature  and  economic  data. The results  show that the Russia-Uk raine war had a significant impact on world crude oil prices, although other factors such as oversupply and reduced demand due to the COVID-19 pandemic also play an important role in determining crude oil prices.  Therefore,  it is necessary to carry out a holistic  and continuous  evaluation of the various  factors  that affect  world crude oil prices,  including regional or geopolitical conflicts. This study provides a better view of how the Russo-Uk rainian war affected world crude oil prices and  provides  suggestions  for  a  more  comprehensive  evaluation  in the  future.  Based  on  the results  of  this  research,  it  is  hoped  that  it  can  become  information  and  input  for lecturers, researchers,  practitioners,  and all interested parties at the Faculty of Engineering, Bhayangk ara University,  Jak arta Raya.